2017
DOI: 10.1016/j.inffus.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Using ensembles for problems with characterizable changes in data distribution: A case study on quantification

Abstract: Ensemble methods are widely applied to supervised learning tasks. Based on a simple strategy they often achieve good performance, especially when the single models comprising the ensemble are diverse. Diversity can be introduced into the ensemble by creating different training samples for each model. In that case, each model is trained with a data distribution that may be different from the original training set distribution. Following that idea, this paper analyzes the hypothesis that ensembles can be especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…In fact, many experiments (Barranquero et al, 2013(Barranquero et al, , 2015González et al, 2017c) have shown that off-the-shelf classifiers are often suboptimal when applied directly to quantification tasks. For that reason, several quantification algorithms have been proposed during the past few years (Firat, 2016;Narasimhan et al, 2016;Pérez-Gállego et al, 2017. A review of quantification learning can be found in González et al (2017b).…”
Section: Quantification Algorithmsmentioning
confidence: 99%
“…In fact, many experiments (Barranquero et al, 2013(Barranquero et al, , 2015González et al, 2017c) have shown that off-the-shelf classifiers are often suboptimal when applied directly to quantification tasks. For that reason, several quantification algorithms have been proposed during the past few years (Firat, 2016;Narasimhan et al, 2016;Pérez-Gállego et al, 2017. A review of quantification learning can be found in González et al (2017b).…”
Section: Quantification Algorithmsmentioning
confidence: 99%
“…Active learning approaches allows the learning algorithm to choose the data it wants to get labels, which is suitable in settings where the 650 labels are costly to obtain. It has been applied in various machine learning applications such as information fusion [45,46], speech recognition, information extraction [47] and text classification [48]. In credibility assessment, active learning approaches can be classified into two categories: classifier-independent and classifier-specific.…”
Section: Related Workmentioning
confidence: 99%
“…The AC correction (32) is sometimes unstable, despite it theoretically returns perfect estimations. When the estimates of tpr and f pr are inaccurate, the correction will cause inappropriate changes [Forman 2008;Pérez-Gállego et al 2017] (this is in part the motivation of the methods in Section 6.5). Using ensembles reduces both risks: the risk of having a bad single classifier and the risk of a poor posterior correction.…”
Section: Ensembles For Quantification Learningmentioning
confidence: 99%